Pengaruh Laju Alir dan Material Pipa Bersambung pada SP-V PT X terhadap Analisis Profil Aliran Fluida dengan Metode Computational Fluid Dynamic (CFD) - Raihan, Raudhatul; Irwan, Irwan; Safitri, Aida (Jurnal Teknologi, 2025)
Piping system is a system that is widely used to move fluids, either liquid, gas, or a mixture of liquid and gas from one place to another, pipes have various sizes and cross-sectional shapes. Pipe branching is widely used in piping systems in industry, mining, and drinking water distribution. Fluid flow profiles and Pressure drop in pipes are very important to know in order to design piping systems. This study was conducted with the aim of determining through simulation the factors that influence the fluid flow profile and pressure drop in the PT X connected pipe with the help of the Computational Fluid Dynamics (CFD) application. The software used in this study is Autodesk Inventor, Autodesk Simulation CFD. the largest pressure drop occurs in the API 5L CS Grade B sch 80 pipe material with 150 L/hour of 14.2467 Psi. while the lowest pressure drop occurs in the API 5L CS Grade B sch 40 pipe material with 70 L/hour of 11.3882 Psi, this is in accordance with the theory that explains that the smaller the diameter of a pipe, the greater the pressure drop will be, due to the difference in inner diameter between the API 5L CS Grade B sch 40 and sch 80 pipe materials. While the largest Power Density occurs in the API 5L CS Grade B sch 40 pipe material with a pipe inner diameter of 6.065 inches of 98969.15297 W/m3. While the lowest Power Density occurs in the API 5L CS Grade B sch 80 pipe material with a pipe inner diameter of 5.6377 inches of 64404.690385 W/m3.